Inhibition of rabies virus transcription in rat cortical neurons with the dissociative anesthetic ketamine. - Lockhart, B P (1992)
In a previous study (B. P. Lockhart, H. Tsiang, P. E. Ceccaldi, and S. Guillemer, Antiviral Chem. Chemother. 2:9-15, 1991), we demonstrated an antiviral effect of the general anesthetic ketamine for rabies virus in neuronal cultures and in rat brain. This report describes an attempt to determine at what level ketamine acts on the rabies virus cycle in rat cortical neuron cultures. Immunofluorescence and [35S]methionine labelling of infected neurons showed that ketamine (1 to 1.5 mM) inhibited viral nucleoprotein and glycoprotein syntheses. Northern (RNA) blots of total RNA from drug-treated neurons, hybridized with 32P-labelled oligonucleotide probes for rabies virus nucleoprotein, matrix protein, and glycoprotein genes, showed a marked reduction (5- to 11-fold) in the levels of rabies virus mRNAs, relative to those in untreated neurons. No significant change in the levels of cellular beta-actin mRNA were detected in ketamine-treated cells. A similar antiviral effect was observed with MK-801; however, no inhibition of rabies virus synthesis was observed with the general anesthetic chloral hydrate. The antiviral effect was not complete; a time-dependent recovery of viral transcription and rabies virus protein synthesis was observed, but no infectious virus was released into the culture supernatant. The lack of any modification of cellular protein or mRNA synthesis by ketamine suggests an antiviral mechanism acting at the level of rabies virus genome transcription.